2021
DOI: 10.1117/1.jbo.26.8.086003
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal multispectral imaging system with cloud-based machine learning algorithm for real-time screening and detection of oral potentially malignant lesions and biopsy guidance

Abstract: . Significance: Screening and early detection of oral potentially malignant lesions (OPMLs) are of great significance in reducing the mortality rates associated with head and neck malignancies. Intra-oral multispectral optical imaging of tissues in conjunction with cloud-based machine learning (CBML) can be used to detect oral precancers at the point-of-care (POC) and guide the clinician to the most malignant site for biopsy. Aim: Develop a bimodal multispectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…For this purpose, it was used a hand‐held widefield BMIS of LEDs emitting at 405, 545, 575, and 610 nm and a 5 MPx monochrome camera. Results indicated a sensitivity of 97.5% and specificity of 92.5% to differentiate OPMDs from normal samples and concluded that their system is suitable for biopsy guidance and early detection of oral cancers 35 …”
Section: Clinical Evidence On Ai and Opmdsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this purpose, it was used a hand‐held widefield BMIS of LEDs emitting at 405, 545, 575, and 610 nm and a 5 MPx monochrome camera. Results indicated a sensitivity of 97.5% and specificity of 92.5% to differentiate OPMDs from normal samples and concluded that their system is suitable for biopsy guidance and early detection of oral cancers 35 …”
Section: Clinical Evidence On Ai and Opmdsmentioning
confidence: 99%
“…The use of multispectral images has also been employed as a diagnostic method to assist the oral medicine specialists 35 . Subhash and collaborators developed a bimodal imaging system which combines tissue, autofluorescence, and diffuse reflectance.…”
Section: Clinical Evidence On Ai and Opmdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research groups are attempting to establish diagnostic criteria, or a form of "optical biopsy", based on the correlation between the histology and optical signatures of tissues, for a variety of human tissues, such as colon [9][10][11], skin [12][13][14], breast [15][16][17][18][19][20], cervical [21][22][23], oral [23][24][25][26][27], prostate [28][29][30][31], nasopharynx [32,33] and lung tissues [34][35][36][37]. Studies have also showed the potential of probe-based DRS to discriminate between human liver tumors and tumor-free surrounding tissue [7,8,[38][39][40][41][42][43].…”
mentioning
confidence: 99%